Prevalence and ergonomic risk profiling of musculoskeletal pain in medical imaging students: a basis for prevention and intervention. - Harun, Hanna Yasmin; Musa, Liyana (IIUM Press, 2025)
Background: Musculoskeletal pain (MSP) is a common problem among university students, particularly those in health-related programmes with significant physical and ergonomic demands during clinical training, and medical imaging students are likely to be similarly affected. The objectives of this study were to identify the risk factors associated with MSP, evaluate its prevalence, frequency, and severity, as well as examine the correlation between MSP frequency and potential risk factors among medical imaging students. Methods: A cross-sectional study was conducted using a validated questionnaire. Descriptive statistics and Spearman's correlation were used to analyse the correlation between MSP and potential risk factors. Results: The results showed that the most frequently affected body regions were the shoulders (49.2%), lower back (38.1%), and neck (36.5%), with both acute (short-term)and persistent(long-term)pain reported. MSP frequency(past 12 months)showed significant correlations with clinical-task-related variables, particularly repetitive motions (ρ=0.787), extended standing (ρ=0.683), and incorrect postures (ρ=0.744). In contrast, lifestyle factors such as sleep duration and stress management showed weaker associations. Conclusion: These findings highlight the need for ergonomic training and preventive strategies to reduce the risk of MSP among medical imaging students. Future studies should examine long-term effects and evaluate intervention strategies to improve clinical performance and student well-being.